Differential Generalized Inverse Demand System estimation (DGIDS) for animal protein in rural areas in Iran - mohammad Ghorbani; komeil mahjori karmozdi (Rāhburdhā-yi tusi̒ah-i rūstāyī, 2016)
Management will make a decision on the future market when economic interrelationships are considered as biological relationships. This paper presents a Differential Generalized Inverse demand system to explore the market of foods containing animal protein and the relationships between different strains of food market existing in the market are discussed in detail. Statistics needed to support the company's affairs and the livestock Statistical Yearbook of Agriculture from 1974 to 2011 was used. Inverse demand system estimated generalized differential (GIDS) and test compound coefficients show that the best model for studying the demand for food containing protein villages in the country is the IAIDS model. The results showed that compensation cross elasticity indices estimated in the inverse demand substitution indicates IAIDS milk and eggs as well as meat and poultry. Quantitative Elasticity indices following theoretical foundations based on compensation were negative. This means increase in the price of any commodity its consumption drops. Meat and milk are essential products for rural consumers. The results of using the Allen elasticity of substitution also show that poultry is the best substitute for milk and vice versa. Also, poultry is the best substitute for red meat and red meat is the best substitute for eggs.